Probabilistic downscaling of GCM scenarios over southern India. (8th May 2012) - Vigaud, N.; Vrac, M.; Caballero, Y.
Abstract: The cumulative distribution function transform (CDF‐t) is used to downscale daily precipitation and surface temperatures from a set of Global climate model (GCM) climatic projections over southern India. To deal with the full annual cycle, the approach has been applied by months, allowing downscaled projections for all seasons. First, CDF‐t is validated over a historical period using observation from the Indian Meteorological Department (IMD). Resulting high resolution fields show substantial improvements compared to original GCM outputs in terms of distribution, seasonal cycle and monsoon means for arid, semi‐arid and wetter regions of the subcontinent. Then, CDF‐t is applied to GCM large‐scale fields to project rainfall and surface temperature changes for the 21st century under the IPCC SRES A2 scenario. The results obtained show an increase of rainfall, mostly during the monsoon season, while winter precipitation is reduced, and suggest a widespread warming especially in the winter and post‐monsoon season. Copyright © 2012 Royal Meteorological Society